HUBUNGAN PENGETAHUAN IBU TENTANG ASI EKSKLUSIF TERHADAP PERILAKU IBU DALAM PEMBERIAN ASI EKSKLUSIF DIWILAYAH KERJA PUSKESMAS MONGOLATO KECAMATAN TELAGA KABUPATEN GORONTALO - Zuriyati Muhamad; Harismayanti Harismayanti (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Breastfeeding is the first food, main, and best for the baby, and natural. Breastfeeding contains a variety of nutrients needed in the process of growth and development of the baby. Unfortunately, the understanding of mothers, families, and communities about the importance of breastfeeding for the baby is lack. As the result, the program of exclusive breastfeeding is not optimum. Breastfeeding is one way to connect the inner soul between mother and children. The purpose of this study was to determine the relationship between mother’s knowledge about exclusive breastfeeding and mother’s behavior on exclusive breastfeeding in the work area of Mongolato Medical Center, Telaga District, Gorontalo Regency. The study design used was a descriptive cross-sectional design. Population and sample are all mothers with infants aged 1 to 2 years who live in the work area of Mongolato Medical Center, Telaga District, Gorontalo Regency. The number of population was 53 mothers and the sample taken was 44 mothers. Sampling technique used was total sampling technique. The result show that there is a relationship between mother’s knowledge about exclusive breastfeeding and mother’s behavior on exclusive breastfeeding in the work area of Mongolato Medical Center, Telaga Disctrict, Gorontalo Regency.This study is expected to add the experience and insight of the researcher especially in terms of research on mother’s knowledge about exclusive breastfeeding and mother’s behavior and also as a reference and comparison for future researches.